Healthcare Workforce Burnout and Wellbeing in the Post-COVID Era: A Bibliometric Analysis of Leadership and Management Research (2021–2025) - Shubba, Shreesha (International Journal of Atharva, 2026)
Background: The issue of the health care workforce’s well-being has become a global priority, especially in the post-COVID-19 period. The rise of burnout, job satisfaction decline, and psychological distress among health care professionals has become a major challenge to health care workforce retention, quality of care, and sustainability of health care systems. The recent literature on health care workforce well-being has moved from individual-level to organizational-level perspectives, including health care management and HRM. However, due to the exponential growth of publications, it is challenging to identify the research trends, thematic priorities, and collaborative networks in this area.Objectives: The aim of this study is to identify the global research landscape related to healthcare workforce burnout, wellbeing, and job satisfaction, with a focus on leadership, healthcare management, and HRM. The objectives of the study were to examine the publication trends, identify the dominant and emerging themes, and examine the leading journals, as well as the co-authorship network at the author, institution, and country levels.Methods: A bibliometric research design was used with gold open-access journal articles retrieved from Dimensions.ai. The search strategy involved the use of keywords associated with healthcare workforce, burnout/wellbeing/job satisfaction, and management/leadership/HRM. The articles were limited to those published between 2021 and 2025. Descriptive statistics, word cloud analysis of article titles and abstracts, source title analysis, and co-author network visualization were conducted using VOSviewer.Findings: The findings reveal a dramatic and continuous trend in the number of publications, particularly after 2022. Keyword analysis shows that the themes of burnout, job satisfaction, leadership, nursing, and hospital settings dominate the literature, emphasizing the importance of organizational and managerial factors in explaining workforce issues. Nursing and health service publications show the highest volume of publications, whereas general public health publications show higher citation impact. Co-authorship networks reveal high international collaboration, particularly between the US and Europe, and increasingly from Asia, the Middle East, and low and middle-income countries.Conclusion: This is supported by the bibliometric data, which shows that the concept of healthcare workforce well-being is no longer viewed purely in terms of the individual but is instead recognized as being influenced by systemic and organizational factors such as leadership, HRM, and organizational culture. It is clear that the field has matured into a globally collaborative, management-focused, and policy-relevant research domain.Novelty: This study offers one of the most comprehensive bibliometric analyses of the phenomenon of burnout and wellbeing in the healthcare workforce in the post-pandemic period, using gold open-access literature and explicitly incorporating the perspectives of leadership and healthcare management. It also points out gaps in the research that are of relevance to low-income or developing countries like Nepal.